Seeing the forest through many trees: Multi-taxon patterns of phylogenetic diversity in the Atlantic Forest hotspot - Brown, Jason L.; Paz, Andrea; Reginato, Marcelo; Renata, Cecilia Amaro; Assis, Claydson; Lyra, Mariana [UNESP]; Caddah, Mayara K.; Aguirre-Santoro, Julian; d'Horta, Fernando; Raposo do Amaral, Fabio; Goldenberg, Renato; Lucas Silva-Brandao, Karina; et al. (Wiley-Blackwell, 2020)
Aim We combine phylogenetic and point locality data from selected lineages of the Atlantic Forest flora and fauna to compare spatial patterns of biodiversity sustained by the current configuration of forest remnants to a scenario of complete forest preservation. We then ask the question how much biodiversity is likely lost, already? Specifically, we assess how habitat loss likely impacted the climatic spaces occupied by the local species, the inferred composition of local communities and the spatial distribution of phylogenetic diversity and endemism. Location Atlantic Forest, Brazil. Methods Using carefully curated point localities, phylogenetic data and parameterized models of species distributions, we generate maps of phylogenetic diversity, phylogenetic endemism and phylogenetic turnover for the entire Atlantic Forest. We map patterns of clade-specific diversity under complete preservation of forest and then incorporate present-day deforestation patterns to provide a more realistic scenario. Results Instead of a singular pattern, three different reoccurring syndromes described the flora and fauna of the Atlantic Forest. These patterns emerged irrespectively of clade age and life history traits. General turnover patterns were highly consistent with previous analyses of species composition and panbiogeographical studies. Deforestation has altered the availability of climatic spaces in the Atlantic Forest, its biological communities and the distribution of evolutionary lineages in space. However, approximately 60% of the pre-Columbian climatic space persists in forest remnants, and today's biological communities are estimated to be 45% similar to pre-deforestation times. Main conclusions The Atlantic Forest has been reduced to 8% of its once largely continuous range. However, the disproportionately large amounts of climate, community and lineage diversity that persist in remnants provide hope and support for conservation efforts that combine species occurrence and phylogenetic data. Inclusion of evolutionary thinking into strategic approaches to restoring Brazilian ecosystems could further conservation effectiveness by incorporating the adaptive potential of local assemblages in the face of further environmental shifts.
Keywords: Atlantic Forests; biogeography; comparative analyses; phylogenetic endemism; phylogenetic turnover; South America; spatial patterns